Gendered pictorial in Indonesian EFL textbook “When English rings the bells” - Wiraningsih, Putu; Suwastini, Ni Komang Arie; Padmadewi, Ni Nyoman (Journal of Education and Learning (EduLearn), 2025)
Sustainable development goal (SDG) 4 and 5 prioritize equal opportunities for all genders and socioeconomic backgrounds to get education. Textbook shapes students' perspectives on gender roles and possibilities for themselves and others thus playing a pivotal role in promoting equality and diversity in education. However, certain English as a foreign language (EFL) textbooks still uphold such biases in their content and images. Thus, this study aimed at describing the gender pictorial in the EFL textbook “When English rings the bells”. Applying textual along with multimodal analysis, this study analyzes the textbook following Pierce’s semiotics. Providing an in-depth analysis of how gender is represented, this study discovered that the textbook still perpetuates gender stereotypes in three areas: i) pictorial of the characters, ii) gender attributes, and iii) traditional roles. It also makes efforts to break these stereotypes by portraying diverse professions and activities. Hence, it may be inferred that the textbook made an effort to analyze and dismantle the notion of gender, yet ultimately reinforced existing preconceptions. It suggests that students can be encouraged to challenge traditional gender roles and aspire to a broader range of careers and life choices by promoting more diverse representations of males and females in textbooks.